２波長光源を用いた吸光体深さ推定の実験的検証 - 清水, 孝一; 岡崎, 恵祐; 加藤, 祐次 (Transactions of Japanese Society for Medical and Biological Engineering, 2015)
The depth-dependent point spread function (PSF) is useful to improve the transillumination image blurred by the strong scattering in body tissue. We have proposed a technique to estimate the depth of an absorber by the PSF convolution of the images in different wavelengths. To evaluate the effectiveness of this technique, experiments were conducted. An absorber was placed at 2 mm depth in a scattering medium with 40 mm thickness. The proposed technique was applied to the images at 760 nm and 800 nm wavelengths. A correlation peak was observed near the given depth of the absorber. In these analyses, the feasibility of the proposed technique was verified.